An adaptive energy monitoring system for a hybrid power plant using renewable energy - Girija, Girija Sankar Panigrahi; Anjan, Anjan Kumar Sahoo (TESEA, transactions on energy systems and engineering applications, 2025)
Classical power plants powered by fossil fuels produce significant amounts of Greenhouse and toxic gases, together with additional environmentally harmful contaminants. Consequently, the greatest solution for the current issue is a power plant based on renewable resources. Researchers strongly advocate hybrid power plants (HPP) since environmental factors affect the affordability of renewable energy sources of a specific place as well as the time of availability. The present study emphasizes on developing an inventive model for a hybrid system using batteries, solar and wind energy that regulates the power generation as well as distribution according to the affordability of clean energy sources which satisfies load demand, charges or discharges the battery, and injects or utilizes grid power and/or electricity. The MALTAB/Simulink platform has been used to model and simulate the suggested hybrid power station and the EMS.